Gold recovery and migration mechanism in the copper smelting and converting (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
The gold embedded in the copper concentrate is enriched in the matte phase during copper smelting and transferred into blister copper during subsequent processing, via which the gold was recycled. In the copper smelting, gold dissolved and appeared as Au (Ⅲ) in the formed gold-matte solid solution. This solid solution could be formed in two ways: by exchanging Au atoms for Cu atoms in the Cu5FeS4 (matte) crystal lattice and by doping Au atoms in Cu5FeS4. In the matte converting, the transfer of gold from the matte phase to blister copper occurred spontaneously due to a fact that the surface tension between the gold and matte phases was considerably higher than that between the gold and copper phases. Gold capture by blister copper occurred by Au atoms replacing Cu atoms in the Cu cell.
Keywords: Gold recycle; Migration behavior; Copper smelting and converting; Structure of gold-matte and gold-copper solid solution